Career Choice Motivational Profiles in First Year University Students - García-Ripa, María Inés (Pontificia Universidad Javeriana, 2018)
This study examines the career choice motivations of first year students in the Catholic University of Argentina (UCA) and describes a classification of the student characteristics that are associated with these motivations.  A questionnaire was designed and validated for this purpose. The factor analysis renders three motivational dimensions: (1) Self-fulfilment and altruism; (2) Search for prestige and economic welfare; and (3) Avoidance motivation. The instrument has been applied to the first year cohort at UCA in the academic year 2013/14 (a total of 1156 students from different disciplines). The existence of differentiated student groups resulting from scores in the motivational scales has been demonstrated. The resulting predictive model can be purposed to guide interventions that are mindful of students’ motivations and needs in a particular context.